A Qualitative Study of Communication between Young Women with Disorders of Sex Development and Health Professionals. (12th January 2015) - Sanders, Caroline; Carter, Bernie
Abstract : Background and Objectives. Health communication is a critical aspect of care for both providers and recipients having a direct influence on engagement and outcomes. Communicating which in this context includes talking and listening in order to share information or support young women to understand their DSD can be difficult especially since the topic area is sensitive. Methods. In this qualitative study thirteen young women (aged 14–19 years) with a disorder of sex development who engaged with health care professionals were purposively recruited between 2011 and 2012 from three specialist centres across the United Kingdom. The young women either were interviewed or completed a diary about their experiences of communication with a range of health care professionals. An interpretative phenomenological approach was used to analyse these data. Results. By analysis of data the young women were able to clearly articulate the qualities and skills health professional needed in relation to communication. Two main categories focused on the duty in which professionals have to share information and their role in supporting young women to manage this information. Discussion and Conclusion. The study results revealed that these young women with a DSD expected to meet skilled professionals who could recognise the emotional aspects of dialogues in the short and longer term.